A Note on Human Capital and the Feldstein-Horioka Puzzle - Margarita Katsimi; Thomas Moutos (Kiel Institute for the World Economy (IfW), 2007)
In this paper we reexamine the Feldstein-Horioka finding of limited international capital mobility by using a broader view (i.e., including human capital) of investment and saving. We find that the Feldstein-Horioka result is impervious to this change.
Keywords: Q4; F2; I2; E2; 330; human capital; current account; investment-saving correlation; capital mobility